Guanfacine Extended Release in the Treatment of Attention-Deficit/Hyperactivity Disorder in Children and Adolescents: A Narrative Review - Czarnecka, Sofia; Łuczyńska, Gabriela; Banatkiewicz, Joanna; Deka, Emilia; Domińczak, Jan; Dobosz, Adam; Bartkowska, Oliwia; Babik, Karolina; Bojanowska, Hanna; Wojnowski, Antoni (Journal of Education, Health and Sport, 2026)
Attention-deficit/hyperactivity disorder (ADHD) is a prevalent neurodevelopmental disorder in children and adolescents and is associated with substantial functional impairment. Although psychostimulants are considered first-line pharmacotherapy, a significant proportion of patients experience inadequate response, poor tolerability, or contraindications to stimulant use. Consequently, non-stimulant medications remain an important component of ADHD management. Guanfacine extended release (GXR), a selective α2A-adrenergic receptor agonist, is approved for the treatment of pediatric ADHD and represents a well-established non-stimulant option. Evidence derived from randomized controlled trials, meta-analyses, and systematic reviews indicates that GXR is effective as monotherapy and as adjunctive therapy to psychostimulants in children and adolescents aged 6–17 years. Across studies, GXR demonstrates clinically meaningful reductions in core ADHD symptoms compared with placebo, with reported effect sizes generally ranging from 0.5 to 0.8. The most commonly reported adverse events are sedation-related symptoms, including somnolence and fatigue, which are typically mild to moderate and tend to decrease with ongoing treatment. Cardiovascular effects are usually modest and consist mainly of small reductions in blood pressure and heart rate, with clinically significant events occurring infrequently. Overall, available data indicate that guanfacine extended release is an effective and generally well-tolerated non-stimulant treatment for ADHD in pediatric and adolescent populations. Its clinical utility is particularly relevant in patients with insufficient response or intolerance to stimulants, as well as in those requiring adjunctive pharmacotherapy. Further studies are warranted to evaluate long-term outcomes and to better define its comparative effectiveness in specific clinical subgroups.